2015
DOI: 10.1016/j.ijdevneu.2015.03.005
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evidence that sulfite impairs glutamatergic neurotransmission and inhibits glutathione metabolism‐related enzymes in rat cerebral cortex

Abstract: Sulfite oxidase (SOX) deficiency is an inherited neurometabolic disorder biochemically characterized by tissue accumulation and high urinary excretion of sulfite and thiosulfate. Affected patients present severe neurological dysfunction accompanied by seizures, whose pathophysiology is poorly known. In the present study we evaluated the in vitro effects of sulfite and thiosulfate on important parameters of glutamatergic neurotransmission and redox homeostasis in rat cerebral cortex slices. We verified that sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 43 publications
0
9
0
1
Order By: Relevance
“…However, it has been shown that sulfite, the main accumulating metabolite in both disorders, is neurotoxic. Sulfite undergoes auto‐oxidation in vitro and in vivo in rat brain, leading to the formation of reactive species 9 and impairing redox homeostasis and antioxidant defenses 9‐14 . Moreover, sulfite disrupts mitochondrial bioenergetics and biogenesis and induces mitochondrial permeability transition, 11,15 as well as glial reactivity and neuronal loss in rat striatum 11 …”
Section: Introductionmentioning
confidence: 99%
“…However, it has been shown that sulfite, the main accumulating metabolite in both disorders, is neurotoxic. Sulfite undergoes auto‐oxidation in vitro and in vivo in rat brain, leading to the formation of reactive species 9 and impairing redox homeostasis and antioxidant defenses 9‐14 . Moreover, sulfite disrupts mitochondrial bioenergetics and biogenesis and induces mitochondrial permeability transition, 11,15 as well as glial reactivity and neuronal loss in rat striatum 11 …”
Section: Introductionmentioning
confidence: 99%
“…In shopper mutants sulfite accumulates (Fig. 4d ) which is reported to inhibit glutamate dehydrogenase (Gdh) or Glutamine synthetase in mammalian cells (Gs) 28 , 29 . Thus, shopper might influence glutamate homeostasis in the ensheathing glia.…”
Section: Resultsmentioning
confidence: 97%
“…Sulfite oxidase oxidizes neurotoxic sulfite that originates from the catabolic metabolism of sulfur containing amino acids. Thus, impaired sulfite oxidase activity results in accumulation of sulfite which suppresses the activity of glutamate dehydrogenase, glutamate transporters, and glutamine synthetase 28 , 29 . Here, we identified Shopper due to its specific function in ensheathing glial cells.…”
Section: Introductionmentioning
confidence: 99%
“…酰化起到抗衰老作用 [41] . 谷胱甘肽代谢能够促进机体 对毒素的排泄, 能够有效清除体内自由基, 可预防帕 金森疾病 [42,43] , 提高机体免疫力. 嘌呤代谢参与阿尔茨 海默病 [44,45] 、帕金森 [46] 、痛风等疾病 [47] , 能够有效降…”
Section: 材料与方法unclassified